The effect of vitamin C in adults with sepsis: a meta-analysis of randomized controlled trials - Luo, Xing; Zhu, Youfeng; Zhang, Rui; Zhu, JianQiu; Kuang, Huanming; Shao, Yuebin; Guo, Xinmin; Ning, Bo (Frontiers in Medicine, 2023)
Background The effect of intravenous (IV) vitamin C in the treatment of sepsis remains controversial. We aimed to explore the clinical efficacy of vitamin C in the treatment of sepsis. Methods Electronic databases (PubMed, Embase, Web of Science, and Cochrane Library) were searched from inception through November 15th, 2022, for randomized controlled trials evaluating the effect of IV vitamin C treatment in patients with sepsis. The primary outcome was short-term mortality, secondary outcomes included duration of vasopressor use, length of intensive care unit (ICU) stay, and Sequential Organ Failure Assessment (SOFA) score after vitamin C treatment. Subgroup analyses were performed based on the dose and duration of IV vitamin C and region to determine whether vitamin C benefited patients with sepsis. Results A total of 10 studies including 1,426 patients fulfilled the predefined criteria and were analyzed. Overall, there were no significant differences between the vitamin C group and the control group regarding short-term mortality [odds ratio (OR), 0.61; 95% confidence interval (CI) 0.37–1.01; p = 0.05], ICU length of stay [mean difference (MD), −1.24; 95% CI -3.54 to 1.05, p = 0.29] and SOFA score (MD, −0.85, 95% CI -2.38 to 0.67, p = 0.27). However, vitamin C significantly reduced the duration of vasopressor use (MD, −14.36, 95% CI −26.11 to −2.61, p = 0.02). Furthermore, subgroup analysis found that in developing countries, vitamin C was associated with a significant reduction in short-term mortality (OR, 0.33; 95% CI 0.12–0.90; p = 0.03), duration of vasopressor use (MD, −24.37, 95% CI -33.72 to −15.02, p < 0.001) and SOFA score (MD, −2.55, 95% CI -4.81 to −0.28, p = 0.03). Conclusion In our study, vitamin C administration for sepsis patients was not associated with a significant reduction in short-term mortality, length of ICU stay or SOFA score. However, we observed that vitamin C could reduce the duration of vasopressor use. Furthermore, sepsis patients in developing countries may benefit more from vitamin C administration than those in developed countries. Systematic review registration: Identifier CRD42022380958, https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=380958.